2017
DOI: 10.2196/mededu.6304
|View full text |Cite
|
Sign up to set email alerts
|

Social Media in Health Science Education: An International Survey

Abstract: BackgroundSocial media is an asset that higher education students can use for an array of purposes. Studies have shown the merits of social media use in educational settings; however, its adoption in health science education has been slow, and the contributing reasons remain unclear.ObjectiveThis multidisciplinary study aimed to examine health science students’ opinions on the use of social media in health science education and identify factors that may discourage its use.MethodsData were collected from the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…The relatively small size of participants in this study also raises a question about the generalisability of their findings. To overcome this limitation, it might be worthwhile conducting similar research across a number of different institutions in the UK, or even internationally, like O'Sullivan et al 38 Similarly, this study replied on self-reported data so there is the potential for errors or subjective bias in their responses.…”
Section: Limitationsmentioning
confidence: 99%
“…The relatively small size of participants in this study also raises a question about the generalisability of their findings. To overcome this limitation, it might be worthwhile conducting similar research across a number of different institutions in the UK, or even internationally, like O'Sullivan et al 38 Similarly, this study replied on self-reported data so there is the potential for errors or subjective bias in their responses.…”
Section: Limitationsmentioning
confidence: 99%
“…Environmental constraints can inhibit actual behavior despite the presence of the intention [ 13 ]. Legal policies are emphasized as a critical factor in not sharing clinical images and content on social media channels by health care students [ 27 , 35 ]. The perceived usefulness and social interaction are the primary motivators for HCPs to join a virtual community of practice; however, time limitations are regarded as a barrier against use [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Furthermore, an international study of SM in health sciences found that there was little instruction in the mainstream education of health sciences students on how to securely and appropriately engage with digital media, and this was echoed in the present study. 10 Roughly half of the students in the current study indicated that they were unsure, while 44% indicated that they knew of an institutional SM policy. This was very different in the ALS provider cohort, where 79% of respondents indicated that they knew of an organisational SM policy.…”
Section: Social Media Policiesmentioning
confidence: 71%